Detection of alteration in carotid artery volumetry using standard-of-care computed tomography surveillance scans following unilateral radiation therapy for early-stage tonsillar squamous cell carcinoma survivors: a cross-sectional internally-matched carotid isodose analysis - Efstratios Koutroumpakis; Mohamed A. Naser; Abdallah Sherif Radwan Mohamed; Salman A. Eraj; Andrea Jarre; Jay C. Shiao; Mona Kamal; Subha Perni; Jack P. Phan; William H. Morrison; Steven J. Frank; G.Brandon Gunn; et al. (Clinical and Translational Radiation Oncology)
Aim: This study leveraged standard-of-care CT scans of patients receiving unilateral radiotherapy (RT) for early tonsillar cancer to detect volumetric changes in the carotid arteries, and determine whether there is a dose–response relationship. Methods: Disease-free cancer survivors (>3 months since therapy and age > 18 years) treated with intensity modulated RT for early (T1-2, N0-2b) tonsillar cancer with pre- and post-therapy contrast-enhanced CT scans available were included. Patients treated with definitive surgery, bilateral RT, or additional RT before the post-RT CT scan were excluded. Isodose lines from treatment plans were projected onto both scans, facilitating the delineation of carotid artery subvolumes in 5 Gy increments (i.e. received 50–55 Gy, 55–60 Gy, etc.). The percent-change in sub-volumes across each dose range was examined. Results: Among 46 patients, 72 % received RT alone, 24 % induction chemotherapy followed by RT, and 4 % concurrent chemoradiation. The median interval from RT completion to the latest, post-RT CT scan was 43 months (IQR 32–57). A decrease in the volume of the irradiated carotid artery was observed in 78 % of patients, while there was a statistically significant difference in mean %-change (±SD) between the total irradiated and spared carotid volumes (−7.0 ± 9.0 vs. + 3.5 ± 7.2, respectively, p < 0.0001). Chemotherapy use, in addition to RT, was associated with a significant mean %-decrease in carotid artery volume compared to RT alone. No significant dose–response trend was observed in the carotid artery volume change within 5 Gy ranges. Conclusions: Our data show that standard-of-care oncologic surveillance CT scans can effectively detect reductions in carotid volume following RT for oropharyngeal cancer. Changes were equivalent between studied dose ranges, denoting no further dose–response effect beyond 50 Gy.